2016
DOI: 10.1111/1346-8138.13420
|View full text |Cite
|
Sign up to set email alerts
|

Sister Mary Joseph's nodule: Malignant transformation of umbilical endometriosis

Abstract: Journal of Dermatology 2016; : 1-2 ovarian biopsy did not reveal malignancies other than the umbilical nodule. The malignant transformation of umbilical endometriosis has been reported only twice, including the present case. Therefore, additional cases are needed to estimate the prognosis. In our patient, physical examinations, blood tests, and ultrasound and CT scans will be performed every 3 months, according to the follow-up protocol for gynecological cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
2
6
0
1
Order By: Relevance
“…In the secondary survey, 2 cases of malignant transformation were noted among the 5 patients (Table 4). The case report forms of these 2 patients evealed that 1 patient had endometrioid adenocarcinoma and the other had adenocarcinoma, identical to an already published case study [5]. In the other 3 patients, whether the malignant transformation of the umbilical endometriosis occurred was not determined.…”
Section: Malignant Transformationsupporting
confidence: 72%
“…In the secondary survey, 2 cases of malignant transformation were noted among the 5 patients (Table 4). The case report forms of these 2 patients evealed that 1 patient had endometrioid adenocarcinoma and the other had adenocarcinoma, identical to an already published case study [5]. In the other 3 patients, whether the malignant transformation of the umbilical endometriosis occurred was not determined.…”
Section: Malignant Transformationsupporting
confidence: 72%
“…As a preoperative imaging test, positron emission tomography (PET)-CT was reported to be useful for the diagnosis of malignancy. 54,55…”
Section: Umbilical Endometriosismentioning
confidence: 99%
“…The histological types were clear cell carcinoma in one case, endometrioid carcinoma in one case, and adenocarcinoma in two cases. As a preoperative imaging test, positron emission tomography (PET)‐CT was reported to be useful for the diagnosis of malignancy 54,55 …”
Section: Abdominal Wall Endometriosismentioning
confidence: 99%
“…16 Koguchi-Yoshioka et al reported a primary adenocarcinoma arising from umbilical endometriosis in a 45-year-old lady in 2016. 14…”
Section: Discussionmentioning
confidence: 99%